Validation of A Preoperative Scoring System to Predict Difficult Laparoscopic Cholecystectomy: A Nepalese Perspective - Baral, Suman; Thapa, Neeraj; Chhetri, Raj Kumar (Journal of Lumbini Medical College, 2020)
DOI: https://doi.org/10.22502/jlmc.v8i1.323 Introduction: Preoperative prediction of the factors leading to difficulty or conversion in cholecystectomy could help plan the surgical strategies and possible outcomes beforehand. The present study aimed to predict and analyze risk factors using a scoring system deemed responsible for surgical difficulties in patients undergoing cholecystectomy for symptomatic cholelithiasis. Methods: This hospital based prospective study was conducted at Department of Surgery, Lumbini Medical College and Teaching Hospital, Nepal. Various factors considered preoperatively were gender, age, previous history of hospitalization, impacted stone, obesity, gall bladder wall thickness, pericholecystic collection, previous abdominal scar and palpable gall bladder. Results: Among 177 cases operated, the mean age ±SD of the patients was 47.72±17.54 years. Conversion rate was 7.9 %. At preoperative score of 5; sensitivity, specificity, positive predictive value and negative predictive value were 89.40% (CI: 83.36%-93.82%), 69.23% (CI: 48.21 %-85.67%), 94.41%(CI: 90.44%-96.79%) and 52.94% (CI: 39.85%-65.64%) respectivelyArea under curve– 0.74, p=0.0001, CI (0.637-0.846). Multivariate analysis showed abdominal scar p=0.02, OR (CI): 5.2 (1.2-21.8), previous hospitalization p=0.001, OR(CI): 6.8(2.2-20.8) and thickened gall bladder wall p= 0.03, OR(CI): 3.6(1.1-11.5) to be statistically significant risk factors. Conclusion: With possible prediction beforehand, high risk group of patients can be identified and dealt accordingly to generate good surgical outcome avoiding complications.